In vivo screen of Plasmodium targets for mosquito-based malaria control - Alexandra S. Probst; Douglas G. Paton; Federico Appetecchia; Selina Bopp; Kelsey L. Adams; Tasneem A. Rinvee; Sovitj Pou; Rolf Winter; Esrah W. Du; Sabrina Yahiya; Charles Vidoudez; Naresh Singh; et al. (Nature, 2025)
Abstract The decline in malaria deaths has recently stalled owing to several factors, including the widespread resistance of Anopheles vectors to the insecticides used in long-lasting insecticide-treated nets (LLINs)1,2. One way to mitigate insecticide resistance is to directly kill parasites during their mosquito-stage of development by incorporating antiparasitic compounds into LLINs. This strategy can prevent onward parasite transmission even when insecticides lose efficacy3,4. Here, we performed an in vivo screen of compounds against the mosquito stages of Plasmodium falciparum development. Of the 81 compounds tested, which spanned 28 distinct modes of action, 22 were active against early parasite stages in the mosquito midgut lumen, which in turn prevented establishment of infection. Medicinal chemistry was then used to improve antiparasitic activity of the top hits from the screen. We generated several endochin-like quinolones (ELQs) that inhibited the P. falciparum cytochrome bc 1 complex (CytB). Two lead compounds that targeted separate sites in CytB (Qo and Qi) showed potent, long-lasting and stable activity when incorporated and/or extruded into bed net-like polyethylene films. ELQ activity was fully preserved in insecticide-resistant mosquitoes, and parasites resistant to these compounds had impaired development at the mosquito stage. These data demonstrate the promise of incorporating ELQ compounds into LLINs to counteract insecticide resistance and to reduce malaria transmission.